Persepsi tentang Kanker Serviks dan Upaya Prevensinya pada Perempuan yang Memiliki Keluarga dengan Riwayat Kanker - Susi Rio; Eunike Sri Tyas Suci (Fakultas Kedokteran, Kesehatan Masyarakat dan Keperawatan UGM, 2017)
Background: Cervical cancer has become a major problem in women’s health not only causing morbidity but also leading to many deaths. Data released by Center for Data and Information Ministry of Health of the Republic of Indonesia showed that in 2013 there were 98,692 patients with cervical cancer in Indonesia the Increasing was mortality of cervical cancer is thought due to delay in handling.Objective: This study was aimed to see a comprehensive perception of cervical cancer and prevention efforts in women who had families with a history of cancer.Method: The approach used in this study was a qualitative approach in which the datas were collected through in-depth interviews and observations.Results and Conclusions: The results of this study showed all five informants perceived cervical cancer as a malignant disease. They found themselves at risk for cervical cancer as well. Four of 5 informants said they would seek immediate preventive measures, but only two of them had made prevention efforts. One informant who, despite believing cervical cancer as a malignant disease and aware of the risks of this disease, and knowing there were efforts that could be done to avoid cervical cancer stated she would not make any prevention efforts.Keywords: woman psychology, woman body, married woman, woman reproductive health, cervical cancer, health belief model (HBM)